THE STRUGGLE OF RELIGIOUS CONSERVATISM AND TERRORISM: CHALLENGES TO INDONESIA'S ISLAMIC MODERATION - umam, Shohebul (JURNAL SETIA PANCASILA, 2022)
The multidimensional crisis caused by the Covid-19 pandemic has pushed for the strengthening of Islamic conservatism, which is one way that makes it easier for terrorism to enter and develop in society. In the midst of a conservative society towards religion, terrorist groups circulate the narrative of Covid-19 as an 'end of time' condition that must be faced with militant jihad, and has proven to be effective in the recruitment process, propaganda, to be effective in mobilizing emotions to carry out acts of terror. The method used is qualitative with a literature study approach through collecting data on reports and literature from previous research results, as well as online news. This study has identified that terrorist groups have successfully adapted to the conditions of the Covid-19 pandemic, and made the pandemic a new issue and inspiration in recruiting, propaganda, and terrorizing acts. Therefore, governmentagencies related to terrorism prevention must be able to develop strategies that are adaptive to this new situation, where so far the approach to counter terrorism has so far been ad hoc. Therefore, the deradicalization policy is not only realized in the form of reorientation and resocialization, but is also encouraged to build counter narratives with terrorism groups in implanting radical ideologies, through new steps, collaborating with mainstream mass organizations such as NU and Muhammadiyah in building a narrative of Islamic moderation, both culturally and through new internet channels.